Prevalence of Respiratory Symptoms and Risk Factors Among Street Sweepers in Gondar City Northwest, Ethiopia, 2021: A Cross-Sectional Study. (December 2022) - Worede, Eshetu Abera; Brhan Alemaw, Helen; Feleke, Hailemariam; Engdaw, Garedew Tadege
Background: Street sweepers are exposed to a variety of risk factors such as dust, bioaerosols, and volatile organic matter, which are responsible for the development of various respiratory symptoms and lung function impairments. However, there is a limited data on the prevalence of respiratory symptoms and associated factors among street sweepers in Ethiopia, especially in the study area. Objective: This study aimed to assess the prevalence of respiratory symptoms and associated factors among street sweepers in Gondar town, northwest Ethiopia, in 2021. Methods: Using simple random sampling technique, a total of 391 workers were selected between August 10 and September 15, 2021. The data was entered and analyzed using the Epi Info Version 7 and Statistical Package for Social Science (SPSS) 22 software, respectively. Descriptive statistics, bivariable, and multivariable logistic regression model were used. P  ⩽ .05 and adjusted odds ratios (AOR) with 95% confidence interval (CI) were used to declare the statistical significance. Result: A total of 391 respondents, with a response rate of 99.2% participated. The prevalence of respiratory symptoms among street sweepers was 35.3% (95% CI: 30.2, 40.5). History of respiratory illness (AOR = 7.75, (95% CI: 3.45, 17.45), washing personal protective equipments (PPE) after use (AOR = 4.77; 95% CI: 2.02, 11.28), previous work in cement (AOR = 3.10, 95% CI: 1.32, 7.34), and flour factories (AOR = 2.13, 95% CI: 2.02, 4.43), and alcohol drinking (AOR = 3.77, 95% CI: 1.94, 7.29) were associated with respiratory symptom among street sweepers. Conclusion: The overall prevalence of respiratory symptoms among street sweepers was 35.3%. Previous respiratory illness, washing personal protective equipment after use, previous work in a cement and flour factory, and drinking alcohol were independently associated with respiratory symptoms. To reduce the respiratory symptoms among street sweeper, it is advisable implementing safe work practice measures and behavioral changes among workers.